Regenerasi Pemain Musik Kecapi Dalam Kesenian Gamad Di Sanggar Seni Gamad Desa Ujung Padang Kecamatan Kota Mukomuko - Fitri Yulia Eka Wulanda; Esy Maestro (SENDRATASIK UNP, 2022)
This study aims to find and describe how the regeneration of kecapi music players carried out at the Gamad Studio, Ujung Padang Village, Mukomuko City District. This type of research is descriptive qualitative. The main instrument in this study is the researcher himself and is assisted by supporting instruments such as stationery and a camera. The type of data used is primary data. Data collection techniques were carried out using literature study, observation, interviews, and documentation. The results showed that the regeneration of lute music players in the Gamad Art Studio, Ujung Padang Village, Mukomuko City District was carried out openly. Regeneration is openly carried out by teaching lute music to family members, the community, and members of the studio. The harp music is the main accompaniment of the Art of Gamad Mukomuko. Gamad's art is packaged in an art package that includes dance, drama, and music performed all night long. The ultimate goal of a harp music training process at Sanggar Gamad, Ujung Padang Village, is to give birth to a new generation that is proficient in playing the kecapi musical instrument.